Biofabrication of a Functional Tubular Construct from Tissue Spheroids Using Magnetoacoustic Levitational Directed Assembly. Issue 24 (18th August 2020) - Parfenov, Vladislav A.; Koudan, Elizaveta V.; Krokhmal, Alisa A.; Annenkova, Elena A.; Petrov, Stanislav V.; Pereira, Frederico D. A. S.; Karalkin, Pavel A.; Nezhurina, Elizaveta K.; Gryadunova, Anna A.; Bulanova, Elena A.; Sapozhnikov, Oleg A.; Tsysar, Sergey A.; et al.
Abstract: In traditional tissue engineering, synthetic or natural scaffolds are usually used as removable temporal support, which involves some biotechnology limitations. The concept of "scaffield" approach utilizing the physical fields instead of biomaterial scaffold has been proposed recently. In particular, a combination of intense magnetic and acoustic fields can enable rapid levitational bioassembly of complex‐shaped 3D tissue constructs from tissue spheroids at low concentration of paramagnetic agent (gadolinium salt) in the medium. In the current study, the tissue spheroids from human bladder smooth muscle cells (myospheres) are used as building blocks for assembling the tubular 3D constructs. Levitational assembly is accomplished at low concentrations of gadolinium salts in the high magnetic field at 9.5 T. The biofabricated smooth muscle constructs demonstrate contraction after the addition of vasoconstrictive agent endothelin‐1. Thus, hybrid magnetoacoustic levitational bioassembly is considered as a new technology platform in the emerging field of formative biofabrication. This novel technology of scaffold‐free, nozzle‐free, and label‐free bioassembly opens a unique opportunity for rapid biofabrication of 3D tissue and organ constructs with complex geometry. Abstract : A combination of intense magnetic and acoustic fields can enable rapid levitational bioassembly of complex‐shaped 3D tissue constructs from tissue spheroids at low concentration of paramagnetic agent (gadolinium salt) in the medium. In the current study, the tissue spheroids from human bladder smooth muscle cells (myospheres) are used as building blocks for assembling the tubular 3D constructs.